Raves, drugs and experience: drug use by a sample of people who attend raves in Western Australia - Lenton, Simon; Boys, A.; Norcross, K. (1997)
Aims. To investigate the patterns of drug use among a sample of people in the rave scene in Perth, Western Australia and test the hypothesis that those who were less experienced in their drug use had less drug-related knowledge.Design.Respondents were recruited through flyers in cafes, clothing and music stores and through snowballing.They were paid $20 for a 1.5 hour interview which comprised both qualitative and quantitative components. Setting. Respondents were interviewed in cafes or restaurants, private dwellings, agencies or other public spaces. Participants. Eighty-three people who had been to a rave in the prior 6 months. Their mean age was 18.9 years (range 13 plus or minus 48) and 53% were male. Measurements. Brief history of drug use, HIV risk behaviour, knowledge of drug-related harm and side effects experienced from drugs.Findings. The group was unremarkable apart from their drug use. Ninety per cent of respondents had ever used LSD,76% had used ecstasy and 69% had used amphetamines.Before, during or after the last rave attended 52% used cannabis and 35% had used each of amphetamines and LSD. Those who were less experienced in their drug use had less knowledge about drugs. Many respondents began using "dance drugs" while they were still at school. Conclusions. Those with less drug-using experience may have less drug-related knowledge and may be at greater risk of harm. Strategies should be implemented which involve people in the scene, promoters,health workers and the authorities to reduce drug-related harm associated with raves and other dance events.